Could Individual Variability in Resistance to Cryopreservation (“Freezability”) Serve as a Biomarker Reflecting Boar Fertility? - Eduardo de Mercado; Helena Nieto-Cristóbal; Adrián Martín-San Juan; María José Martinez-Alborcia; Manuel Álvarez-Rodríguez (Animals)
Subfertile boars often go undetected until they cause significant reproductive losses. Current semen quality assessments are limited in their ability to predict fertility, highlighting the need for complementary biomarkers. This study explored whether semen freezability could serve as an indirect indicator of boar fertility. Eighteen boars were classified based on historical fertility records and semen freezability, assessed by post-thaw quality. Fresh and post-thaw semen samples were analyzed using the CASA system and fluorescence microscopy. High-fertility boars showed significantly better motility and functional sperm parameters in fresh semen compared to low-fertility boars. However, these differences were mostly lost after cryopreservation. Conversely, boars with good freezability had consistently better post-thaw semen quality, though this did not correlate directly with higher fertility outcomes. Notably, a combined analysis revealed that boars with both high fertility and poor freezability had the lowest post-thaw semen quality. This suggests that cryopreservation may expose hidden sperm defects not detectable in fresh semen. Total motility was the only parameter associated with both fertility and freezability. In conclusion, while freezability alone may not directly predict fertility, it may help identify low-performing males. The combined assessment of fresh semen motility and freezability could support more effective boar selection strategies.